E-159 Feasibility and safety of transradial access for pediatric neurointerventions. (4th August 2020) - Srinivasan, V; Hadley, C; Prablek, M; Lopresti, M; Chen, S; Peterson, E; Sweid, A; Jabbour, P; Young, C; Levitt, M; Osbun, J; Burkhardt, J; et al.
Abstract : Background: Diagnostic cerebral angiograms are increasingly being performed by transradial access (TRA) in adults, following in line with data from the coronary literature supporting fewer access-site complications. Despite this ongoing trend on TRA in neuroangiography, there has been no discussion of its use in the pediatric population. In fact, pediatric TRA for other endovascular intervention has scarcely been described even for coronary or other applications. This is the first dedicated study of transradial access for neuroangiography in pediatric patients. Methods: A multi-institutional series of consecutively performed pediatric transradial angiograms and interventions was collected. This included demographic, procedural, outcomes, and safety data. Data was prospectively recorded and retrospectively analyzed. Results: A total of 37 diagnostic angiograms and 24 interventions were performed in 47 pediatric patients, by 5 neurointerventionalists. Proximal and distal angiography were performed successfully for both diagnostic and interventional application (19 distal angiograms, 2 distal interventions). Clinically significant vasospasm occurred in 7 patients (11.5%). Re-access was successfully performed in 7 patients a total of 11 times. Conversion to femoral access occurred in 6 cases (9.8%). There were no access-related complications otherwise. Conclusions: Transradial access in pediatric patients is safe and feasible. It can be performed successfully in many cases but carries some unique challenges compared to the adult population. Despite the challenge of higher rates of vasospasm and conversion to transfemoral access, it is worth exploring further, given the potential benefits. Disclosures: V. Srinivasan: None. C. Hadley: None. M. Prablek: None. M. Lopresti: None. S. Chen: None. E. Peterson: None. A. Sweid: None. P. Jabbour: None. C. Young: None. M. Levitt: None. J. Osbun: None. J. Burkhardt: None. J. Johnson: None. P. Kan: None.